RESORT HOTEL DI PANTAI ANGSANA - Pratiwi, Bella; Hartono, Rudi (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
The human need for recreation from the saturation of urban activities is very supportive of the development of the tourism sector, especially natural tourism which brings natural beauty. But until now there are still a few tourist attractions that are able to accommodate and facilitate vacation activities for tourists, as well as a lack of human awareness of the environment. The emergence of a problem can be helped with programming methods as a problem-solving. To produce a natural tourism sector that is environmentally friendly and can accommodate all vacation activities according to predetermined standards. The results of the resort building design use a sustainable concept where the building is designed so as not to damage the surrounding environment and save energy.